(untitled) (Хабаршы. Психология және социология сериясы, 2022)
The culture of consumption of comics by the young generation is actualized by a wide range of preconditions and consequences in the formation of brutal thinking due to imitation of the favorite char- acters in the comic book industry. The aim of the study is to define comics as the leading agent of social- ization of generation “Z”, to elucidate the nature of violence in comics and anime through determining the degree of popularity of superheroes, supervillains and antiheroes among the younger generation of Kazakhstan. The aim of the study is to determine comics as the leading agent of socialization of genera- tion Z and in this direction to find out the essence of violence in comics and anime, to determine the degree the popularity of superheroes, supervillains and antiheroes among the younger generation of Ka- zakhstan. The main results of the research show the fact that the products of the comic book industry are perceived by the younger generation as the norm and consequently reflected in the aggression towards peers. Consumers of the comic book industry are becoming more obedient and reverent to authoritative directors, with little or no opinion on their creations. The instincts of the younger generation transform their inner state depending on what they see on the screen. In the world of comics, a logic of good and evil is formed, which has equal forces of opposition. The viewer is given the choice of which side to take. The paradox is that antiheroes and supervillains have more admirers than some superheroes. The binary logic of the comic book industry creates an imbalance in the mindset of a teenager. The study of the problem is based on a sociological survey of 600 respondents. Key words: violence, media comics, comics industry, superheroes, supervillains, antiheroes.